Generalized discrete fourier transform based minimization of PAPR in OFDM systems - Elshirkasi, Ahmed Mohamed; Siddiqi, Mohammad Umar; Habaebi, Mohamed Hadi (IEEE Explore, 2014)
Orthogonal frequency division multiplexing OFDM is a preferred technique in digital communication systems due to its benefits of achieving high bit rates and its ability to resist multipath effect over fading channels. However, high peak to average power PAPR ratio of the OFDM transmitted signal is a main drawback in OFDM systems. In this paper, the nonlinear phase from the theory of generalized discrete Fourier transform (GDFT) is used to improve the performance of the partial transmit sequence (PTS) scheme which is one of the techniques used to reduce PAPR. This technique divides the input OFDM block into a number of sub-blocks. IFFT is taken for each sub-block, then the output phase is rotated by coefficients to produces minimum PAPR. Simulation results show that modifying the phase of the OFDM before applying the technique reduces the number of the sub-blocks for the same amount of PAPR reduction.